Improving the Stability of Organic–Inorganic Hybrid Perovskite Light‐Emitting Diodes Using Doped Electron Transport Materials. Issue 20 (19th July 2019) - Kim, Taejun; Kim, Jin-Hoon; Triambulo, Ross E.; Han, Hyowon; Park, Cheolmin; Park, Jin-Woo
Abstract : Herein, organic–inorganic hybrid perovskite light‐emitting diodes (PeLEDs) are fabricated under ambient air and all‐solution conditions. A novel N2 gas blowing step is applied during spin‐coating of the precursor solution to obtain uniform methylammonium lead bromide (MAPbBr3 ) perovskite nanocrystal films with fewer surface and interfacial defects than solution‐processed perovskite films. Furthermore, polyethylenimine (PEI) and poly[9, 9‐dioctyl‐9′, 9′‐bis[3‐(trimethylammonio)propyl][2, 2′‐bi‐9 H ‐fluorene]‐7, 7′‐diyl] (PFN) are used as doping agents in the widely used electron transport layer (ETL) material, 2, 2′, 2″‐(1, 3, 5‐benzinetriyl)‐tris(1‐phenyl‐1‐ H ‐benzimidazole) (TPBi), and act as passivation agents between the rough surface of the perovskite film and the ETL. Consequently, the high surface work function of PEI‐ and PFN‐doped TPBi results in reduced and balanced injection of electrons in the perovskite light‐emission layer (EML) of the PeLEDs, producing a maximum luminance ( L ) up to 14 358 and 11 465 cd m −2 for the PEI‐ and PFN‐based PeLEDs, respectively. The doped‐ETL‐based PeLEDs also show a 3.6 times longer L 50 (i.e., the time needed for a 50% reduction in the initial value of L operated at 4 V) than the pure TPBi‐based PeLEDs, which need a separate poly(methyl methacrylate) (PMMA) film to act as the passivation layer between the EML and ETL. Abstract : A novel N2 gas blowing method is used to achieve a uniform perovskite layer morphology. Polyethylenimine (PEI)‐ and poly[9, 9‐dioctyl‐9′, 9′‐bis[3‐(trimethylammonio)propyl][2, 2′‐bi‐9 H ‐fluorene]‐7, 7′‐diyl] (PFN)‐doped 2, 2′, 2″‐(1, 3, 5‐benzinetriyl)‐tris(1‐phenyl‐1‐ H ‐benzimidazole) (TPBi) achieve a maximum luminance ( L ) up to 14 358 and 11 465 cd m −2, respectively. The doped‐electron transport layer (ETL)‐based perovskite light‐emitting diodes (PeLEDs) exhibit an improved lifetime of 3.6 times longer L 50 than the pure TPBi‐based PeLEDs.